The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1373/clinchem.2014.234369
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sex on the Prognostic Value of High-Sensitivity Cardiac Troponin I in the General Population: The HUNT Study

Abstract: BACKGROUND:A new, high-sensitivity assay for cardiac troponin I (hs-cTnI) permits evaluation of the prognostic value of cardiac troponins within the reference interval. Men have higher hs-cTnI concentrations than women, but the underlying pathophysiological mechanisms and prognostic implications are unclear. The aim of this study was to assess the potential impact of sex on the association between hs-cTnI and cardiovascular death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
87
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 39 publications
8
87
1
3
Order By: Relevance
“…Moreover, the cutoff of high-sensitivity cTn that was applied in our study exceeds age-and sex-specific cutoffs that have been advocated for diagnosis of MI. [34][35][36] Third, 41% of the enrolled AIS patients received intravenous thrombolysis before coronary angiography, which may lead to improved TIMI flow rates. In the Strategic Reperfusion Early After Myocardial Infarction (STREAM) trial, a significantly higher rate of TIMI III flow was found in patients with ST-segment elevation MI randomized to fibrinolysis before percutaneous coronary intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the cutoff of high-sensitivity cTn that was applied in our study exceeds age-and sex-specific cutoffs that have been advocated for diagnosis of MI. [34][35][36] Third, 41% of the enrolled AIS patients received intravenous thrombolysis before coronary angiography, which may lead to improved TIMI flow rates. In the Strategic Reperfusion Early After Myocardial Infarction (STREAM) trial, a significantly higher rate of TIMI III flow was found in patients with ST-segment elevation MI randomized to fibrinolysis before percutaneous coronary intervention.…”
Section: Discussionmentioning
confidence: 99%
“…13 Mortality status was also obtained for all participants as previously reported. 11 Data are given as either median (IQR) or absolute numbers (proportion). Continuous variables were analysed using the Mann-Whitney U test and the Kruskal-Wallis Test, and categorical variables with the Pearson Chi-Square test and the Fisher exact test, where appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10] More recent studies show a profound sex difference in the prognostic ability of hsTnI on cardiovascular death, with an apparent stronger effect in women. 11 However, it remains unclear whether the stronger association between hs-TnI and cardiovascular death in women is based on the ability of hs-TnI to predict myocardial infarction (MI) or HF. To further elucidate this effect of sex, we investigated the association between hs-TnI and incident MI and HF in women and men.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of detection of cTn in a "normal" population of 524 presumably healthy North American individuals ranged from 0-35% with the available assays for both cTnI and cTnT, and only one of those was able to detect cTnI in as many as 96% individuals in that cohort. Despite the frequency of detectable cTn in the general population largely depends on selection criteria (14-16), a very high rate of positivity has been observed in ensuing studies carried out in representative samples of the general population (17)(18)(19)(20), as well as in the pediatric age (21,22) (Figure 1).…”
mentioning
confidence: 99%